Social-life cycle assessment as an extended tool for the measurement of the social responsibility in the agro-food sector - Benedetto, Graziella (Italian Review of Agricultural Economics, 2016)
The growing attention of consumers to the social and environmental aspects associated with the production of agro-industrial goods is a key driver for leading companies. The attention to social and environmental issues increases the added value of a company. A useful tool that can measure the Social Responsibility of a business is the Social-Life Cycle Assessment (S-LCA). The aim of this paper is to suggest a better diffusion of the S-LCA implementation in the agri-food sector, since the social dimensions of sustainability have still limited application worldwide. This scope is in line with the literature's recommendation to carry out more case studies to improve the methodology and highlight where the S-LCA is weak. The paper includes two stages: firstly a description of the methodology is proposed; secondly we will present the results of some studies, focused on the agro-industrial sector, to see what information can be drawn from S-LCA implementation.